2012
DOI: 10.1037/a0026206
|View full text |Cite
|
Sign up to set email alerts
|

A latent class regression analysis of men's conformity to masculine norms and psychological distress.

Abstract: How are specific dimensions of masculinity related to psychological distress in specific groups of men? To address this question, the authors used latent class regression to assess the optimal number of latent classes that explained differential relationships between conformity to masculine norms and psychological distress in a racially diverse sample of 223 men. The authors identified a 2-class solution. Both latent classes demonstrated very different associations between conformity to masculine norms and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 41 publications
3
58
0
2
Order By: Relevance
“…Due to shame and stigma, some survivors adopt rigid masculine norms as a coping mechanism (Lisak, 1994), which could undermine long-term mental health. Our analyses found a direct relationship between masculine norms and psychological outcomes across the entire sample, consistent with research in the general population (Alfred et al, 2014; Mahalik & Rochlen, 2006; Wong et al, 2012). However, we did not find a heightened effect of masculine norms among those who were sexually abused.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Due to shame and stigma, some survivors adopt rigid masculine norms as a coping mechanism (Lisak, 1994), which could undermine long-term mental health. Our analyses found a direct relationship between masculine norms and psychological outcomes across the entire sample, consistent with research in the general population (Alfred et al, 2014; Mahalik & Rochlen, 2006; Wong et al, 2012). However, we did not find a heightened effect of masculine norms among those who were sexually abused.…”
Section: Discussionsupporting
confidence: 87%
“…Some men may respond to victimization by overcompensating and adopting hyper-masculine personas in adulthood (Lisak, 1994). Among the general population, however, rigid notions of masculinity have been associated with lower psychological well-being (Alfred, Hammer, & Good, 2014), psychological distress (Wong, Owen & Shea, 2012), depression (Mahalik & Rochlen, 2006), and negative attitudes towards help-seeking (Levant, Wimer, & Williams, 2009). Few studies have examined the relationship between gender norms and mental health for sexually abused men.…”
Section: Literaturementioning
confidence: 99%
“…For example, research has indicated that as men endorse more traditional gender roles they report more depression and anxiety (Mahalik, Locke, et al, 2003), alexithymia , substance abuse (Liu & Iwamoto, 2007;Locke & Mahalik, 2005), interpersonal violence and sexual aggression (Jakupcak, Lisak, & Roemer, 2002), relationship dissatisfaction (Bum & Ward, 2005), and overall psychological distress (Wong, Owen, & Shea, 2012).…”
mentioning
confidence: 99%
“…Regression mixture models have been increasingly applied to different research areas, including marketing (Wedel & Desarbo, 1994, 1995), health (Lanza, Cooper, & Bray, 2013; Yau, Lee, & Ng, 2003), psychology (Van Horn et al, 2009; Wong, Owen, & Shea, 2012) and education (Ding, 2006; Silinskas et al, 2013). While traditional regression analyses model a single average effect of a predictor on an outcome for all subjects, regression mixtures model heterogeneous effects by empirically identifying two or more subpopulations present in the data where each subpopulation differs in the effects of a predictor or predictors on the outcome(s).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the majority of the studies employing regression mixtures gave no information about residual variance specifications whether the equality constraint has been imposed or not (Lanza et al, 2013; Lanza, Kugler, & Mathur, 2011; Liu & Lu, 2011; Schmeige, Levin, & Bryan, 2009; Wong & Maffini, 2011; Wong et al, 2012). The contribution of this paper is to examine the degree to which this is a consequential decision that should be thoughtfully made and clearly reported, so that readers can understand regression mixture results, and so results may be replicated in the future.…”
Section: Introductionmentioning
confidence: 99%